Digital Comic Media Based on Jejaitan Bali Ethnomathematics on Flat Form Material for Class IV Mathematics Students - Prabasari, Jhoti; Gusti Ngurah Sastra Agustika (International Journal of Natural Science and Engineering, 2024)
Mathematics is often considered an abstract subject and difficult for elementary school students to understand, especially flat material. The lack of interesting and contextual learning media makes students less motivated to learn. In fact, mathematics learning can be connected to local culture through an ethnomathematics approach, which can make abstract concepts more meaningful. This research aims to describe the design of digital comic media based on Jejaitan Bali ethnomathematics, determine the feasibility of digital comic media based on Jejaitan Bali ethnomathematics, and determine the effectiveness of digital comic media based on Jejaitan Bali ethnomathematics on flat material. This development research uses the ADDIE development model. The subjects of this research were fourth grade elementary school students with a total of 31 students. The data collection methods used are interviews, observations, questionnaires and tests. The data analysis used is quantitative and qualitative descriptive analysis, as well as inferential statistical analysis. The main results of this research show that digital comic media based on Balinese jejaitan ethnomathematics is effective in increasing understanding of the concept of flat shapes in fourth grade students. The media developed successfully links mathematical concepts with local culture, so that students understand the material more easily through examples that are familiar in their daily lives.  The implications of this research indicate that the integration of local culture into learning media, such as digital comics based on Balinese jejaitan ethnomathematics, can be an effective strategy for increasing understanding of basic mathematics concepts in elementary schools. By utilizing cultural elements that are close to students' lives, learning becomes more contextual, meaningful and interesting, thereby increasing students' motivation and active involvement in the learning process.